La Comunidad como forma de integración y organización entre los sicuris en Buenos Aires - Padin, Esteban Ariel (2018)
This article explores a series practices and narratives in order to analyze the forms in which an Andean musical group is configured as community in the Autonomous City of Buenos Aires, Argentina. The fieldwork consisted of making music together with the group, trying to generate an intersubjective practice that questions the division of traditional empiricism. The community is expressed in values, defined as Andean, that model the types of interaction and organization of the group. These aspects are problematized through the link that the Arco Iris Sicuris Community engages with social organizations. Studying the type of links that the group generates and how the sicuris are organized allows me the reflection about the identity construction of the group and its members in a city historically defined as European and non-indigenous. I arrive at the conclusion that the community allows to build identifications that transform the daily practices of the sicuris, through the combination of ethnicized elements in and from the Buenos Aires City, with visions that establish Arco Iris as a different way of being in the world.